Discourses about the conquest and retaining of Ceuta - Teodoro, Leandro Alves [UNESP] (Editora Puc Minas, 2020)
The second chief-chronicler and chief-keeper of the Torre do Tombo ( National Archives), Gomes Eanes de Zurara, was renowned for writing chronicles full of particulars about the conquest and retaining of Ceuta in the fifteenth century. Seeking to explore the impressions of the royal chronicler, the present work will discuss how Zurara made use of two of his sources: a speech by count D. Pedro de Meneses and, especially, one reportatio by Fr. Joao Xira. More precisely, the aim of this study is to examine to what extent Zurara reproduced the words of these famous figures expecting not only to legitimize the royal military incursion into North Africa, but also to instruct the Portuguese knights and counsel them on their role in society. Without dwelling too much on the character of Zurara, the intent is to analyse the role of the discourse of a clergyman and that of a knight in exhorting the Portuguese soldiers sent to that region, during a period of strengthening of the political and religious bases of Portugal.
Keywords: Gomes Eanes de Zurara; Portuguese chronicles; Moral formation; Fifteenth century